IMPLEMENTASI NILAI-NILAI EXTINCTION REBELLION (XR) GLOBAL OLEH XR RIAU DALAM MEMBANGUN GERAKAN IKLIM DI RIAU - Dermawan, Angelina Puteri; Takwa, Tuah Kalti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study analyzes the implementation of Extinction Rebellion (XR) global values by XR Riau in building a local climate movement amid environmental crises in Riau Province. The focus is on three key values: shared vision of change, mission on what is necessary, and regenerative culture. This research uses a qualitative descriptive approach through interviews and literature review. The results show that XR Riau implements these values through public education, symbolic nonviolent actions, and the development of collective awareness. These values shape movement direction, issue prioritization, and internal sustainability. However, challenges remain, including low public awareness, limited capacity, and safety concerns. Keywords: Extinction Rebellion, XR Riau, Climate Movement, New Social Movement